The Role of Misorientation in Direct Wafer Bonded III-V Materials. (20th July 2018) - Liao, Michael; Tran, Victor; Yee, Matthew; Seal, Mark; Goorsky, Mark S.
Abstract : Wafer bonding represents an important method to study the effects of wafer misorientation, both tilt and twist, on the properties of the bonded interface since both forms of misorientation can be controllably induced. Of particular interest in this study, the impact on electronic transport across the interface can be systematically studied for III-V materials systems. Both twist and tilt between bonded wafers is found to induce additional interfacial energy band bending that impedes electronic transport across the interface. The effect of rotational misalignment is found to exhibit a cyclic behavior, contrary to some studies reported in literature. The findings presented here suggest that crystallographic planar symmetry plays a role in influencing the bonded interface electrical properties.